The Application of the Cooperative Learning Model (Picture and Picture) to Improve the Students’ Reading Skill - Yerdiana Mohibu; Hamid Ismail (Jurnal Langua, 2021)
The purpose of this study was to improve students' reading skills using picture and picture media. This research is a Classroom Action Research. The research was conducted in two cycles. The subjects of this study were 23 students in class IX SMP Kristen Idamgamlamo west Halmahera. The data collection techniques in this study were observation and test. While the data analysis techniques were used The results showed that: The use of picture and picture media can improve students' reading activities. The increase occurred in cycle I is 53,8%. Learning activities were not optimal. The implementation of cycle II is 88,4% causes activity and learning outcomes to be good and increase to a higher level so that it can support quality learning. The conclusion of this research is to improve reading ability by using picture and picture media in class IX SMP Kristen idamgamlamo Halmahera Barat.